1996
DOI: 10.1021/jm9507284
|View full text |Cite
|
Sign up to set email alerts
|

Potent, Cell Active, Non-Thiol Tetrapeptide Inhibitors of Farnesyltransferase

Abstract: All previously reported CAAX-based farnesyltransferase inhibitors contain a thiol functionality. We report that attachment of the 4-imidazolyl group, via 1-, 2-, or 3-carbon alkyl or alkanoyl spacers, to Val-Tic-Met or tLeu-Tic-Gln provides potent FT inhibitors. (R*)-N-[[1,2,3,4-Tetrahydro-2-[N-[2-(1H-imidazol-4-yl)ethyl] -L-valyl]-3-isoquinolinyl]carbonyl]-L-methionine ([imidazol- 4-yl-ethyl]-Val-Tic-Met), with FT IC50 = 0.79 nM, displayed potent cell activity in the absence of prodrug formation (SAG EC50 = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 25 publications
1
46
0
2
Order By: Relevance
“…B1088 (32) was provided by Dr. A. Garcia (Eisai Institute). BMS193269 (33) was provided by Dr. V. Manne (Bristol-Myers Squibb Co.). ␣-Hydroxyfarnesyl-phosphonic acid (34) was purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…B1088 (32) was provided by Dr. A. Garcia (Eisai Institute). BMS193269 (33) was provided by Dr. V. Manne (Bristol-Myers Squibb Co.). ␣-Hydroxyfarnesyl-phosphonic acid (34) was purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these so-called non-thiol farnesyltransferase inhibitors have nitrogen-containing heterocycles, the ring nitrogen of which coordinates the enzyme-bound zinc, similarly to the cysteine thiol group [14]. However, it has been shown that nitrogen heterocycles can be replaced by aryl residues, which lack the ability to coordinate metal atoms, without Using docking studies of model compounds of nonthiol farnesyltransferase inhibitors as well as GRID analyses of the binding region of farnesyltransferase, we have located two different aryl binding clefts in the active site of farnesyltransferase, which we suggest to be the postulated aryl binding regions (Figure 1) [19].…”
mentioning
confidence: 99%
“…The peptidomimetic inhibitors, BMS191563 (22) and B1088 (7), were provided by V. Manne (Bristol-Myers Squibb) and A.M. Garcia (Eisai Research Institute, Andover, MA), respectively. Another peptidomimetic inhibitor, FTI-277 (23), was provided by S. Sebti (University of South Florida) or purchased from Calbiochem.…”
mentioning
confidence: 99%